(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Neonatal suffering is a major health problem in Morocco, as in other countries, and concerns the difficulties encountered by the newborn during the perinatal period. According to the WHO, the causes of this suffering are multiple, including health care, maternal health, access to health services, education and nutrition. Aim This study aims to clarify the epidemiological and anthropometric profile of neonatal suffering in Morocco by analysing 1,416 cases recorded over a five-year period (2019-2023) at the Idrissi Hospital in Kénitra. Result Analysis of Apgar scores, birth weights and foetal aspects reveals a predominance of full-term births (81.9%), with foetal weights mainly between 2,600 and 3,600 grams (50.8%). However, a significant proportion of newborns required resuscitation at birth (85.2%), indicating a high prevalence of perinatal complications. The low Apgar scores at 1 minute, with 58.6% of newborns having a score of less than 6, underline the importance of intensive neonatal monitoring. In addition, the distribution of medical interventions shows that 67.4% of deliveries required interventions such as episiotomy or caesarean section, reflecting proactive management of obstetric risks. In addition, the logistic regression model identified key factors associated with the need for neonatal resuscitation, such as maternal age, number of live babies, 1-minute Apgar score and newborn weight. Conclusion These results underline the importance of rigorous antenatal surveillance, particularly for pregnancies identified as being at risk, in order to prevent neonatal suffering. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 103-110